(untitled) (Journal of Solar Energy Research Updates, 2024)
A comprehensive integrated solar power plant system has been developed to support the operation of a biogas plant based on a heat pump, for which fermented wort is a low-potential energy source. The change in the power factor of the solar power system connected to the grid and the temperature of the coolant entering the heat exchanger built into the methane tank are predicted. Promising solutions include changing the power of the heat pump compressor to maintain biogas production, unloading fermented wort and loading fresh material while maintaining the power factor of the grid solar system and changing the level of electricity transmission to the grid. The voltage at the input of the hybrid inverter, the voltage at the output of the frequency converter to assess their ratio and the voltage frequency are constantly measured. When changing the voltage at the input of the hybrid inverter from 240 V to 600 V, promising solutions were adopted to reduce the power of the heat pump from 3.14 kW to 1.58 kW in the production of biogas 352.5 m3/day to maintain the temperature of the heating coolant entering the heat exchanger built into the methane tank at 55° C - 45 °C in order to obtain biogas, unload fermented wort and load fresh raw materials. There is an increase in the power of electricity transmission to the grid from 0.27 to 1 and an increase in the power factor by 40% from 0.58 to 0.98. The use of the developed Smart Grid technology allows preventing peak loads of the power system, reducing electricity consumption from the grid by up to 30%.